Improving tone production on the flute with regards to embouchure, lip flexibility, vibrato and tone colour, as seen from a classical music perspective - Hinch, John de Courteille (University of Pretoria, 2013)
Dissertation (MMus (Performing Art))--University of Pretoria, 2006.